2008
DOI: 10.1002/art.23415
|View full text |Cite
|
Sign up to set email alerts
|

Low glycosylated ferritin, a good marker for the diagnosis of hemophagocytic syndrome

Abstract: Objective. A very low percentage of glycosylated ferritin (<20%) has only been reported in association with adult-onset Still's disease (AOSD), a disease classically associated with hemophagocytic syndrome. We undertook this study to determine whether hemophagocytic syndrome outside the context of AOSD is also associated with a very low percentage of glycosylated ferritin.Methods. From October 2006 to September 2007, the serum level of glycosylated ferritin was determined in all consecutive patients seen in 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 28 publications
3
45
0
7
Order By: Relevance
“…A recent study by Fardet et al reported that the fraction of glycosylated ferritin is lower in patients with HLH compared with other inflammatory disorders. 30 Further investigation is necessary to validate this observation and identify novel markers of HLH.…”
mentioning
confidence: 95%
“…A recent study by Fardet et al reported that the fraction of glycosylated ferritin is lower in patients with HLH compared with other inflammatory disorders. 30 Further investigation is necessary to validate this observation and identify novel markers of HLH.…”
mentioning
confidence: 95%
“…Although the serum ferritin level fluctuates during systemic inflammation, GF remains low several weeks to months after disease remission [8]. However, a low level of GF is not specific to AOSD; it is observed also in other inflammatory processes like in severe systemic infections [5] or haemophagocytic syndromes [9].…”
Section: Discussionmentioning
confidence: 99%
“…31,33 Low glycosylated Ferritin was found to be useful in assisting the diagnosis in patients with ferritin values between 500 and 10,000 µg/L. 34,35 Bone Marrow (BM) score is based upon number of hemophagocytic cells per high power field, and classified as mild (1-2), moderate (3-5), severe (6)(7)(8), very severe (˃8). 36 Bone marrow finding may be a late manifestation with false negativity if done early.…”
Section: Diagnostic Criteriamentioning
confidence: 99%